2020
DOI: 10.1111/pops.12657
|View full text |Cite
|
Sign up to set email alerts
|

How Nation Building Backfires: Beliefs about Group Malleability and Anti‐Chinese Attitudes in Hong Kong

Abstract: An intriguing phenomenon documented within political science research is the association between nation‐building programs and increased subnational intergroup conflicts. Based on data collected in Hong Kong, an epicenter of subnational conflicts in China, this article suggests that nation building may intensify the tension between subnational groups because it helps to spread the belief that groups have fixed inherent characteristics. Specifically, in the face of deep intergroup cultural and political differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Meanwhile, respondents overall exhibited a rather positive attitude towards immigration ( M = 4.46, SD = 1.45), with 42.6% of them agreeing that the benefits of immigration outweighed the costs for their country. This held true even in Hong Kong and Singapore, where previous studies have reported considerable anti‐immigrant sentiment (e.g., Chang & Welsh, 2016 ; Lee & Chou, 2020 ). In addition, as shown in Table 3 , the two operationalizations of COVID‐19 vulnerability and perceived border stringency were both positively associated with support for immigration.…”
Section: Resultsmentioning
confidence: 68%
“…Meanwhile, respondents overall exhibited a rather positive attitude towards immigration ( M = 4.46, SD = 1.45), with 42.6% of them agreeing that the benefits of immigration outweighed the costs for their country. This held true even in Hong Kong and Singapore, where previous studies have reported considerable anti‐immigrant sentiment (e.g., Chang & Welsh, 2016 ; Lee & Chou, 2020 ). In addition, as shown in Table 3 , the two operationalizations of COVID‐19 vulnerability and perceived border stringency were both positively associated with support for immigration.…”
Section: Resultsmentioning
confidence: 68%
“…The growing bias and hostility of young people in Hong Kong toward mainland China, as evidenced by the massive youth-led protests in Hong Kong in recent years ( Cheng, 2016 ; Veg, 2017 ), have been endangering the existing connections and regional cooperation between Hong Kong and mainland China ( Cheung, 2012 ; Ma, 2015 ; Chan, 2020 ; Lee and Chou, 2020 ). These negative sentiments and the resultant tensions, possibly driven by concerns over Hong Kong’s increasing political and economic dependence on mainland China ( Ma, 2015 ) and the decline of political trust in the Chinese central government in the Hong Kong society ( Steinhardt et al, 2018 ), have had detrimental impacts on regional cooperation between Hong Kong and mainland China, raising tremendous concerns in both regions.…”
Section: Introductionmentioning
confidence: 99%
“…The study was implemented several months after the widespread social upheavals in 2019. The massive, digitally enabled, and increasingly violent conflicts deepened polarization in society (Zhu et al., 2022), with many citizens holding extreme views on political values, group identification, and policy preferences (Lee & Chou, 2020; Wong et al., 2019). Further, we replicated Fernbach et al.…”
Section: Introductionmentioning
confidence: 99%
“…The study was implemented several months after the widespread social upheavals in 2019. The massive, digitally enabled, and increasingly violent conflicts deepened polarization in society (Zhu et al, 2022), with many citizens holding extreme views on political values, group identification, and policy preferences (Lee & Chou, 2020;Wong et al, 2019). Further, we replicated Fernbach et al's (2013) Experiment 1 (Study 3, N = 376) in 2023 to examine whether the relationship between knowledge illusion and extreme positions varies over time after the restructuring of the sociopolitical order.…”
mentioning
confidence: 99%